Mental Health Self-Stigma of Syrian Refugees With Posttraumatic Stress Symptoms: Investigating Sociodemographic and Psychopathological Correlates - Bär, Jonathan; Pabst, Alexander; Röhr, Susanne; Luppa, Melanie; Renner, Anna; Nagl, Michaela; Dams, Judith; Grochtdreis, Thomas; Kersting, Anette; König, Hans-Helmut; Riedel-Heller, Steffi G. (Frontiers in Psychiatry, 2021)
Background: The high prevalence of mental disorders related to posttraumatic stress among Syrian refugees is often in contrast with their low utilization of mental health care in the host countries. Mental health self-stigma, i.e., internalized stigma of having a mental disorder, could prevent individuals from seeking mental health care. Therefore, we aimed to provide evidence on different aspects of mental health self-stigmatization among adult Syrian refugees with posttraumatic stress symptoms residing in Germany. Moreover, we investigated associations with sociodemographic and psychopathological variables in order to identify those at higher risk of self-stigmatization. Material and Methods: Overall, 133 participants with mild to moderate posttraumatic stress symptoms were recruited in the metropolitan areas of Leipzig, Dresden and Halle, Germany, using a multimodal approach. Mental health self-stigma was assessed using the Self-Stigma of Mental Illness Scale – Short Form (SSMIS-SF), consisting of four subscales (Stereotype awareness, Stereotype agreement, Application to self , Harm to self-esteem), each scoring from 5 (low) to 45 (high) points. Linear regression analysis was used to test associations of sociodemographic and psychopathological variables with self-stigma subscales. Results: On average, self-stigma ratings ranged from 16.5 (SD = 6.6) points on Application to self to 28.3 (SD = 7.5) points on Stereotype awareness. Results showed higher scores on Application to self for individuals who were younger (t = 2.65, p = 0.009) and single (F = 5.70, p = 0.004). Regression analyses yielded statistically significant associations between having multiple comorbidities and a higher Application to self stigma (β = 0.18, p = 0.044), controlling for sociodemographic covariates. Discussion: Mental health self-stigma was increased among Syrian refugees in Germany. Correlates of increased self-stigma could inform efforts to improve access to mental health care among Syrian refugees with mental ill-health. Longitudinal studies following an intersectional approach by concurrently examining multiple forms of public and internalized stigma could provide helpful insights for developing tailored stigma reduction efforts in this context.